In the quest for reconceptualising social impacts of resettlement scheme: a critical review / Khairil Afiq Ahmad ... [et al.] - Ahmad, Khairil Afiq; Md Saman, Nor Hisham; Mat Radzuan, Indera Syahrul; Mohd Arip, Mohd Sabri (2021)
A long, persistent, and burning issue in the displacement and resettlement field of study is to identify social impacts variables that are generated from the displacement of project affected people (PAP) at the resettlement schemes. These variables boil down to another critical question which is the risk management and reconstruction model that could be executed to cushion, mitigate, and eliminate the identified social impacts. Ultimately, this review paper intends to unveil each of the model fortes and its trade-off. Driven and guided by the research questions, this study reviews secondary data regarding the models, frameworks, and approaches by paying serious attention to the ways of identifying the relevant social issues of resettlement schemes. The review is made via the content analysis technique which unveils that there are eight (8) parameters in identifying social impacts variables at the resettlement schemes performance: i) landlessness; ii) joblessness; iii) homelessness; iv) marginalization; v) food insecurity; vi) increased morbidity and mortality; vii) loss of access to common property and services; viii) social disarticulation. It is hoped that this paper could provide a better way of reconceptualizing social impacts at the resettlement both in terms of theoretical and empirical sides.